Peningkatan Kompetensi Guru Fisika melalui Pelatihan Pembelajaran Fisika Berbasis STEM - Ali Ismail; Surya Gumilar; Irma Fitria Amalia (Institut Pendidikan Indonesia, 2023)
This community service activity aims to provide skills for physics teachers in Garut district to create STEM-based learning. Through good and proper learning, the delivery of material can be better absorbed by students. So that later students are expected to be easier to understand the concepts. The dedication activity consisted of two stages, the first stage of the socialization and the second phase of training. Socialization and training were followed by MA Physics teachers in Cibatu sub-district. The training material is training on STEM Education, the selection of STEM-based learning models, and assistance in making STEM-based media. The results showed that community service went well and smoothly. Based on the results of the questionnaire as a whole the teachers responded positively related to the implementation of this training. The teacher seemed very enthusiastic in listening to the explanation and practicing what the resource person said. In addition, the teachers stated that through the training, they gained a lot of benefits related to the addition of knowledge about learning alternatives that could be applied in Physics learning, even they felt an increase in creativity in making STEM-based learning and learning media. The obstacles that arise at this stage of the training are the problems of time that are felt to be lacking for training, therefore they give advice to hold ongoing training related to STEM learning.